Survey of progress in chemistry. - Scott, Arthur F. (Academic Press, 1966)
Survey of Progress in Chemistry, Volume 3 considers the principles common to all chemistry that undergo major developments and modifications, including photosynthesis, flame, asymmetric reduction, and stereoregular polymers. This volume is composed of five chapters, and starts with a discussion on component reactions, apparatus, and photoelectron transport of photosynthesis. The next chapter deals with the general chemistry and kinetics of some of the common flame system, along with their practical applications. A chapter focuses on the many mechanistic applications of isotope effects. This to.